THE ENGLISH BLENDING WORDS IN INDONESIANâS NEWSPAPERS - Rafida, Tien (English Department of Faculty of Tarbiyah and Teachers Training, 2016)
Blending offers a unique and unusual character which is frequently used by mass because of its creativityÂ and this study aims to figure out the pattern of English blending words in Indonesianâs newspaper createdÂ and the meanings of those blending words. The study found that the complex words shows the pattern. The pattern of those analyzed complex words are categorized into AB + CD =AD. These patterns are based on Plagâs theory about blending words. The meaning of those complex words was built based on the first and the second words. It follows the pattern of AD, namely the first term (A) and the last term (D) are combined. Â The twenty blending wordsÂ discussed are not common in English itself. It is because these English complex words have been domesticated by Indonesianâs terms.